Public agencies tweeting the COVID-19 pandemic: cross-country comparison of must have and forgotten communication topics - Tagliacozzo, Serena; Albrecht, Frederike; Ganapati, Nazife Emel (Frontiers in Communication, 2023)
Introduction Despite the importance of national-level public health agencies in times of a pandemic, there is limited comparative understanding of their must-have and forgotten pandemic-related communication topics. Methods To fill this gap in the literature, this article presents an analysis of COVID-related communication topics by national-level health agencies in Italy, Sweden, and the United States using the IDEA (Internalization, Distribution, Explanation, Action) model on crisis message framing. The public health agencies included in the study are the Italian National Institute of Health (Istituto Superiore di Sanità; ISS), the Public Health Agency of Sweden (Folkhälsomyndigheten), and the Center for Disease Control and Prevention (CDC) in the US. Results Based on these agencies' Twitter posts (n = 856) in the first 3 months of the pandemic, the article reveals a greater attention paid to action oriented (e.g., disease prevention) and explanatory messages (e.g., disease trends) than to distribution (e.g., transmission) and internalizing messages (e.g., risk factors) in all three countries. The study also highlights differences in terms of referrals to other communication channels and communication topics, especially in terms of these agencies' emphasis on individual risk factors (related to the risk of a person suffering from serious COVID-19-related health consequences) and social risk factors (related to the chance of an individual to become infected with COVID-19 because of the social context). Discussion The study's findings call for better incorporation of information that is directly relevant to the receivers (internalizing messages) by public health agencies.